2003
DOI: 10.1136/vr.152.2.45
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane anaesthesia in chickens during spontaneous and controlled ventilation

Abstract: A crossover study design was used to investigate the dose-related effects of sevoflurane at end-tidal concentrations of 2.2 to 4.4 per cent on the respiratory rate, blood gases, heart rate, arterial blood pressure and ocular signs of chickens during spontaneous and controlled ventilation. The mean (sd) carbon dioxide partial pressure (PaCO2) increased as the concentration of sevoflurane increased, and was 86 (29) mmHg at an end-tidal concentration of 4.4 per cent during spontaneous ventilation, but was maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
20
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 17 publications
11
20
0
Order By: Relevance
“…The MAC value, however, may vary considerably among avian species (Mercado and others 2008) and can be influenced by many physiological factors (body temperature, metabolic rate, blood CO 2 tension and large variations in blood pressure; Quasha and others 1980). In the current study, as in several other studies determining MAC values in birds (Ludders and others 1989, Naganobu and Hagio 2000, Naganobu and others 2003, Kim and others 2011, Escobar and others 2012, Phair and others 2012), body temperature remained stable during all the anaesthetic procedures. Consequently, body temperature was unlikely to have influenced these results.…”
Section: Discussionsupporting
confidence: 88%
“…The MAC value, however, may vary considerably among avian species (Mercado and others 2008) and can be influenced by many physiological factors (body temperature, metabolic rate, blood CO 2 tension and large variations in blood pressure; Quasha and others 1980). In the current study, as in several other studies determining MAC values in birds (Ludders and others 1989, Naganobu and Hagio 2000, Naganobu and others 2003, Kim and others 2011, Escobar and others 2012, Phair and others 2012), body temperature remained stable during all the anaesthetic procedures. Consequently, body temperature was unlikely to have influenced these results.…”
Section: Discussionsupporting
confidence: 88%
“…Both ISO and SEVO resulted in a smooth, rapid induction to and a relatively smooth recovery from anesthesia in captive adult crested serpent eagles, consistent with previous reports in bald eagles, chickens and psittacines [25, 34, 39]. Rapider induction and recovery is desirable following extensive anesthetic periods or in debilitated eagles [35].…”
Section: Discussionsupporting
confidence: 86%
“…Sevoflurane is likely less apt to induce arrhythmias because it does not sensitise the myocardium to catecholamines [37]. In our study, the PaCO 2 at the moment in which the MAD was determined was significantly increased compared with the baseline value in all groups but was compatible with the results obtained in chickens (46 mmHg with 2.2% sevoflurane) [30] and thick-billed parrots (38.6 mmHg with 2.35% sevoflurane) [12]. Moreover, the PaCO 2 values in this study were lower than those reported in ducks (57.2 ± 4.2 and 93.9 ± 11.8 mmHg using 1.0 and 1.5 MAD isoflurane, respectively) [34] and parrots (55.87 mmHg with 3.44% sevoflurane) [16].…”
Section: Discussionsupporting
confidence: 89%
“…A decrease in respiratory rate was observed in all of the groups analysed after determining the MAD (T2) in comparison with baseline (T0), and there were no significant differences among the groups, suggesting that premedication does not significantly potentiate this decrease. The respiratory rates measured after the application of the anaesthetic (T2) were similar to those observed in another study in the same species [16] and in thick-billed parrots [12] and higher than the values observed in chickens [30]. …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation